Avaliação do uso de semicondutores de nitreto de gálio no estágio de controle de potência de uma luminária LED para iluminação pública - Barboza, Igor Bertoncello (2022)
This work presents a comparative analysis in terms of efficiency and losses estimation between a power control (PC) stage of a commercial LED luminaire, which uses Silicon (Si) transistors, with respect to two prototypes that use distinct Gallium Nitride (GaN) transistors for the same application. The work development is presented in details, including the design of the proposed electronic systems, the theoretical losses analysis and experimental validations of both prototypes with GaN transistors. Firstly, a literature review about the structure, working principle, characteristics, advantages and disadvantages of GaN transistors is accomplished, as well as the main existing device types. The review addresses the technological challenges, including the PCB (printed circuit board) layout, thermal management and measurements in GaN transistors. Then the LEDs drivers in the literature are presented, focused on the selected topology, the voltage, current and power levels in the GaN devices, the power density and the efficiency, the type of GaN transistor employed, the switching frequencies and the maximum reached efficiencies. Finally, a comparative analysis of efficiency, losses estimation and its distribution between the main commercial components of the LED driver PC stage is performed. The converters with Si MOSFETs were compared to the Synchronous Buck converters which employ enhancement-mode GaN transistors, developed and implemented in the case study 1, with the monolithic solution MasterGaN1, and in the case study 2, with the discrete solution with GaN transistors of the model GS-065-011-1-L and the external gate drivers. The experimental efficiencies of the GaN-based synchronous buck converters of the case studies 1 and 2, disregarding the auxiliary circuits consumption (including the gate drivers), remained in the range between 96% and 97%, what showed an increase of at least 1% related to the best case compared to the Si MOSFET, in the whole LED load dimming range (10-100%). The discrete solution converter presented bigger efficiency, in nominal power, in comparison to the monolithic, which is a difference around 0.35%. Regarding the GaN devices temperature, the ones of the case study 2 remained in 80.4°C and 85°C, while the monolithic solution presented 90.4°C. An analysis of the losses prediction in GaN-based synchronous buck converters was developed. estimated and experimental va From this prediction, the absolute error lues, were 0.034% and 0. s obtained , between the 122%, respectively, for the case studies 1 and 2. Through the analysis of the losses prediction results of the Buck converters of the reference work, with Si MOSFET, it was observed t hat t the semicon ductor devices, MOSFET and freehe predominance of losses occur wheeling diode, s which concentrate leastw in ise 60% of the GaNSibased converter losses. For another side, the based synchronous buck converters theoretical showed that in theses circuits t losses analysis of the he losses are mainly in the buck converter inductor and correspond to 70% of the losses for both case studies, in nominal power.